Oxygen non-stoichiometry and defect structure of LaMn1-zCuzO3+δ - A. Yu. Zuev; D. S. Tsvetkov (Chimica Techno Acta)
The quantitative model analysis of the defect structure of copper doped lanthanum manganites LaMn1-zCuzO3+δ (z = 0.05 and 0.1) was performed. In the framework of the model, the independent course of the three reactions of defect formation, including the electronic exchange between manganese and copper, completion of a lattice by the absorption of oxygen and the disproportionation of manganese was considered. It is shown that the increase in the dopant content leads to a change in the dominant electronic process. This is reflected in the lock and disproportionation and leads to the increase in the concentration of holes and decrease the concentration of electrons localized on the manganese atoms.